Environmental Factors, Knowledge, and Hygiene Behaviour among Mothers: A Slum Area in Bandung City, West Java, Indonesia - Gusti Adintya Putri; Sri Yusnita Irda Sari; Yoni Fuadah Syukriani (Althea Medical Journal, 2017)
Background: The increased number of population living in urban areas causes the increase of requirement of basic life needs as well as the increase of household and human excreta waste. If these wastes were not well managed, this situation would contaminate the environment. This study aimed to analyze the relatioship between environmental factors, knowledge and hygiene behavior among mothers who lives in Bandung slum area.Methods: An analytic cross sectional study was carried out on 132 mothers who lived in Tamansari subdistrict in Bandung city (RW 06, 07, 15, and 16) from  May to October 2014. The primary data were collected using 2 sets of  questionnaire and an observation checklist. The environmental factors and knowledge variables were catagorized into good and poor, while hygiene behavior was catagorized into good, moderate, and poor. The collected data were statistically analyzed using Chi-Square test.Results: More than half of the participants had good environmental factors (60.6%), 59 participants (44.6%) had good knowledge about hygiene and 83 participants (62.9%) had good hygiene behavior, 43 participants (32.6%) had a moderate hygiene behavior, and 6 participants (4.5%) bad hygiene behavior. Environmental factors was related to hygiene behavior (p=0.002). However, knowledge was not related to hygiene behavior (p=0.539). Conclusions: Environment is a significant factor to hygiene behavior